Eksplorasi Sustainable Development Goals (SDGs) Disclosure Di Indonesia - Agung Prasetyo Nugroho Wicaksono (Jurnal Akademi Akuntansi, 2023)
SDGs (Sustainable Development Goals) is a global development agenda that aims to alleviate problems in the social, economic, environmental, as well as legal and governance fields to ensure the quality of human life in a sustainable manner. This study seeks to explore the disclosure of SDGs in companies from various sectors in Indonesia. Sampling using purposive sampling technique so as to produce 16 companies from 8 sectors as the sample. The analysis method uses content analysis in the 2021 sustainability report which is then explored using matrix coding on Nvivo. The results show that the level of disclosure of the SDGs in Indonesia is very low with an average of 8% based on business action and 20% based on SDGs targets.